2019
DOI: 10.1002/ajpa.23851
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy isotopic analyses of human skeletal material from Rapa Nui: Evaluating the evidence from carbonates, bulk collagen, and amino acids

Abstract: ObjectivesStable isotope ratio analysis of bulk bone collagen dominates research into past diet; however, bone carbonate and compound specific isotope analyses (CSIA) of amino acids provide alternative, yet complementary, lines of evidence toward that same research goal. Together they inform on different aspects of diet, allowing greater certainty in reconstructions. Here we present new data on carbonate isotopes for Rapa Nui and reevaluate prehistoric diet in the context of these new and previously published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 93 publications
3
27
0
Order By: Relevance
“…Thus, rather than resulting in a reduction in productivity, the available data indicate that deforestation and the establishment of agricultural infrastructure increased the overall carrying capacity of the island and represent sustainable subsistence strategies. Moreover, recent isotopic analyses of human remains from archaeological deposits show a broad and varied diet from terrestrial and marine resources [40,107,108]. In sum, our current understanding of Rapa Nui subsistence practices indicates adaptation and resilience to environmental risk and uncertainty.…”
Section: Human-environment Interactions On Rapa Nuimentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, rather than resulting in a reduction in productivity, the available data indicate that deforestation and the establishment of agricultural infrastructure increased the overall carrying capacity of the island and represent sustainable subsistence strategies. Moreover, recent isotopic analyses of human remains from archaeological deposits show a broad and varied diet from terrestrial and marine resources [40,107,108]. In sum, our current understanding of Rapa Nui subsistence practices indicates adaptation and resilience to environmental risk and uncertainty.…”
Section: Human-environment Interactions On Rapa Nuimentioning
confidence: 98%
“…Analyses of plant microfossils preserved in the teeth of human remains from archaeological contexts also challenge the assumption that people were consuming resources from palms [104]. The available data point to a dietary focus on dryland cultivation of sweet potato, taro, yams, bananas, and other crops, the consumption of chickens and rats, along with fishing and other forms of marine foraging (e.g., [40,[104][105][106][107][108][109]). So, while parts of the palm may have been consumed at some point in the past, the loss of these sources would not have resulted in significant dietary stress [63].…”
Section: Human-environment Interactions On Rapa Nuimentioning
confidence: 99%
“…Robinson & Stevenson (2017) suggested that some reduction in arable land could have existed due to soil erosion after deforestation, but this would have caused spatial reorganizations of agricultural practices, leading to cultural continuity rather than a population collapse. In addition, some recent anthropological studies have shown that the diet of the postdeforestation Rapanui people was balanced, with no signs of malnutrition (Commendador et al, 2013(Commendador et al, , 2019Polet, 2015;Polet & Bocherens, 2016;Jarman et al, 2017).…”
Section: Resiliencementioning
confidence: 99%
“…Wine and olive oil were major imports from the Levant for upper class consumption with increased demands from the Middle Kingdom (Marcus 2007), though some wine Fig. 1 Location of Tell el-Dab c a in northern Egypt had been produced locally from the Early Dynastic Period (Arnold et al 1995;Cohen 2018;David 1999;Murray 1999). Some prominent C 4 sedges of the Cyperus genus were collected for both human consumption and as fodder (Li et al 1999).…”
Section: Bronze Age Diet In Egyptmentioning
confidence: 99%